Variable Baseline Papio cynocephalus Endogenous Retrovirus (PcEV) Expression Is Upregulated in Acutely SIV-Infected Macaques and Correlated to STAT1 Expression in the Spleen - Maze, Emmanuel Atangana; Ham, Claire; Kelly, Jack; Ussher, Lindsay; Almond, Neil; Towers, Greg J.; Berry, Neil; Belshaw, Robert (Frontiers in Immunology, 2019)
Retroviral replication leaves a DNA copy in the host cell chromosome, which over millions of years of infection of germline cells has led to 5% of the human genome sequence being comprised of endogenous retroviruses (ERVs), distributed throughout an estimated 100,000 loci. Over time these loci have accrued mutations such as premature stop codons that prevent continued replication. However, many loci remain both transcriptionally and translationally active and ERVs have been implicated in interacting with the host immune system. Using archived plasma and tissue samples from past macaque studies, experimentally infected with simian immunodeficiency virus (SIV), the expression of one macaque ERV in response to acute viral infection was explored together with a measure of the innate immune response. Specifically, RNA levels were determined for (a) Papio cynocephalus Endogenous Retrovirus (PcEV), an ERV (b) STAT1, a key gene in the interferon signaling pathway, and (c) SIV, an exogenous pathogen. Bioinformatic analysis of DNA sequences of the PcEV loci within the macaque reference genome revealed the presence of open reading frames (ORFs) consistent with potential protein expression but not ERV replication. Quantitative RT-PCR analysis of DNase-treated RNA extracts from plasma derived from acute SIV-infection detected PcEV RNA at low levels in 7 of 22 macaques. PcEV RNA levels were significantly elevated in PBMC and spleen samples recovered during acute SIV infection, but not in the thymus and lymph nodes. A strong positive correlation was identified between PcEV and STAT1 RNA levels in spleen samples recovered from SIV-positive macaques. One possibility is that SIV infection induces PcEV expression in infected lymphoid tissue that contributes to induction of an antiviral response.